Advances in Models of Fibrous Dysplasia/McCune-Albright Syndrome - Lung, Hsuan; Hsiao, Edward C.; Wentworth, Kelly L. (Frontiers in Endocrinology, 2020)
The Gs G-protein coupled receptor pathway is a critical regulator of normal bone formation and function. The Gs pathway increases intracellular cAMP levels by ultimately acting on adenylate cyclase. McCune-Albright Syndrome (MAS) and fibrous dysplasia (FD) of the bone are two proto-typical conditions that result from increased cellular Gs signaling activity. Both are caused by somatic activating mutations in the GNAS gene that encodes for the Gsα subunit. FD bone lesions are particularly difficult to treat because of their variability and because of the lack of effective medical therapies. In this review, we briefly discuss the key clinical presentations of FD/MAS. We also review the current status of mouse models that target the Gs GPCR signaling pathway and human cellular models for FD/MAS. These powerful tools and our improving clinical knowledge will allow further elucidation of the roles of GPCR signaling in FD/MS pathogenesis, and facilitate the development of novel therapies for these medically significant conditions.